Communication and Aging. - Nussbaum, Jon F. (Communication., 2000)
This text employs a communication perspective to examine the aging process and the ability of individuals to adapt successfully to aging. It continues the groundbreaking work of the first edition, emphasizing a life-span approach toward understanding the.